Inflammatory Bowel Disease - Szabo, Imre (IntechOpen, 2012)
This book is an overview of invited contributions on recent data of inflammatory bowel diseases. The first part of the book covers topics related to the ethiopathogenesis of inflammatory bowel diseases including the environmental, genetic factors and immunological alternations. The next chapters deal with present day management of disease including radiological diagnosis and surgical treatment, which consider the advances of most up-to-date radiological methodology including MRI techniques and the role of surgical procedures in the therapy. The final part presents medical therapy and its future directions. These chapters discuss natural products exerting anti-inflammatory and anti-tumour effects, methods of colon targeting drug delivery systems including polysaccharides, peptides and nanoparticules; as well as the potential risks of nanotechnology based food materials.